Progress in Molecular Characterization and Epitope Identification of Major Buckwheat Allergens - Yufei QIN; Ning YU; Wenhan KANG; Yang LI; Fengxin HU; Jiukai ZHANG; Ying CHEN (Shipin gongye ke-ji)
Buckwheat is a common food allergen that can cause diseases related to the respiratory, digestive, and circulatory systems, and in severe cases, it can lead to anaphylactic shock or even death. Identifying the main allergenic proteins in buckwheat and determining their allergenic epitopes is of great significance for understanding the mechanism of buckwheat allergy and for the prevention and treatment of related allergic diseases. This paper reviews the structural characteristics and research progress on the epitopes of the main buckwheat allergens (Fag e 1, Fag e 2, Fag e 3, Fag e 4, Fag e 5, Fag t 2, Fag t 3, Fag t 6), aiming to provide a reference for in-depth research and prevention of buckwheat allergies.